(untitled) - Pick, James B (Hoboken, N.J, 2008)
Written specifically for the businessperson, Geo-Business: GIS in the Digital Organization is the first book to provide comprehensive coverage of GIS applications in the business and organizational environment. Going beyond a strictly geographical focus, this book sets GIS in the context of business information systems and other business sub-disciplines such as logistics, marketing, finance, and strategic management. It presents from an organizational perspective the advantages of spatially enabling existing enterprise systems and illustrates how GIS is applied in the real world through rigorous case study analyses of twenty companies, including Baystate Health, Chico’s, Kaiser Permanente, Lamar Advertising Company, Rand McNally, Southern Company, Sears Roebuck, and Sperry Van Ness.
Keywords: Management,Business,Quản lý,Kinh doanh; Geographic information systems,Geographic information systems,Hệ thống thông tin địa lý,Hệ thống thông tin địa lý